A (R)EXISTÊNCIA DAS VOCACIONADAS AO MINISTÉRIO PASTORAL BATISTA: DESCORTINANDO A RELAÇÃO ENTRE AS PASTORAS BATISTAS DE SÃO PAULO E A NÃO FILIAÇÃO NA ORDEM DOS PASTORES BATISTAS DO BRASIL EM SÃO PAULO (OPBB-SP) - SOUZA, VALÉRIA VIEIRA DE (2016)
The Baptist context is predominantly marked by male leaders and for women only places and behaviors socially established, such as home care, maternity, submission, among other characteristics that emphasize the gender hierarchy. Even before the economic development and occupation that women are gaining in the public space, the church, mainly Baptist churches, remain founded on foundations that exalt male power at the expense of place that should be occupied by women, or where they decide to act. If they decide to operate in a predominantly male place, they will have to deal with the deconstruction of a thought socially permeated with male domination and the arduous construction of a thought aimed at gender equality. The object of this research is the female pastoral ministry in the Baptist Brazilian context. The text analyzes the discourse of Pastors Baptists of São Paulo and the speech of the Order of the leaders of Baptist Pastors of São Paulo (OPBB-SP) about the female pastoral ministry and not the membership of women in OPBB-SP. The importance of this work is to demonstrate the relationship of the micro power existing between shepherds and shepherdesses and concomitant inequalities within the context Baptist in relation to pastoral ministry. This statement is configured by means of the analysis of semi-structured interviews I conducted research with seven shepherds of São Paulo, as well as three leaders of OPPB-SP. It is a qualitative research, in which were analyzed official documents of the church, as convention agendas, protocol, institutional sites, periodicals and unofficial documents found on social networks, blogs, online newspapers, etc. I can claim that the Baptists pastors are mobilizing to fulfill his calling, using transcendent arguments that prevent any person to challenge or doubt the pastoral call these women, but: “The wind goes were its pleasure takes it, and the sound of it comes to your ears, but you are unable to say where it comes from and where it goes; so it is with everyone whose birth is from the Spirit.” (John 3.8)